Measures To Combat Viral Diseases And Prospects For Their Improvement - Zukhra Nuruzova Abdukadirovna (International Journal of Medical Sciences And Clinical Research, 2025)
The world has seen the rise and reemergence of numerous infectious diseases that were either nonexistent or reemerging in recent decades, for which there are few prompt and efficient prophylactic interventions. In order to develop efficient preventative and therapeutic measures, the WHO has released a list of priority infections that are likely to cause future epidemics. A thorough grasp of the aetiology, epidemiology, and pathophysiology of the target disorders serves as the foundation for the reasoning for these therapies. While it is crucial to recognize the critical role that evolutionary changes in pathogens play, it is just as important to recognize the impact of a complex interaction of circumstances on the emergence and recurrence of infectious diseases. These include shifts in the human population, exposure vectors and reservoirs, and environmental changes. The aetiology, epidemiology, and pathophysiology of the ten WHO priority diseases—including HIV/AIDS, TB, and malaria—as well as those with high epidemic potential that are already the subject of particular control program activities are summarized in this overview. Additionally, this evaluation focused on how public health surveillance and response systems may be used to combat these illnesses. In order to effectively control transmission, such systems must be built to quickly identify odd and unexpected illness patterns, track and communicate information in real time, and mobilize global reactions. In addition to the creation of particular vaccinations, the goal of this narrative review is to explore the literature for antiviral tactics that could slow the spread of infection chains. In the event of future viral pandemics, the suggested interventions—such as the use of TMPSSR2 inhibitors, antiviral mouthwashes, or high-affinity cholinergic ligands—may prevent and treat post-acute infection syndromes in addition to preventing the emergence of viral resistance to vaccines.